Comparison of different body measurement techniques: 3D stationary scanner, 3D handheld scanner, and tape measurement. Issue 8 (3rd August 2019) - Xia, Sibei; Guo, Siming; Li, Jiayin; Istook, Cynthia
Abstract: Body measurements play an import role in pattern generation and size determination. Traditionally, body measurements were captured with tape measures. The tape measure technique is often time-consuming. Nowadays, three-dimensional (3D) stationary whole-body scanners are widely used in the apparel industry to collect body measurements. The stationary scanner has good performance on efficiency, validity, and reliability. However, it is not suitable for home use due to its high cost. Occipital's Structure Sensor, as a representation for low-price handheld 3D scanners, is a 3D scanner for mobile devices. This research focused on studying whether the Structure Sensor could be used to capture body measurements for the apparel industry or not. Its performance was compared to a whole-body stationary scanner and the tape measurement. It was found that the Structure Sensor could be used to collect body measurements data with relatively low reliability if corresponding measurement extraction software was developed.